Technical change and wage premiums amongst skilled labour: Evidence from the economic transition. Issue 1 (25th April 2022) - Alexeev, Sergey
Abstract: I present reduced‐form and structural evidence that the reorganization of the Russian economy in the post‐transitional period increased the demand on law and business graduates. This demand shock provides a novel unified explanation of the Russian wage structure for 1985–2015. I then show that this shock is a common feature of all transitional economies, and it contributed to the transformational recession. The demand behaviour is identified with a new skill‐biased technical change model of demand for skills with three production inputs (high school graduates and bachelor‐level educations with two majors), showing that a technology shift that favours a particular skill might emerge within the skilled group rather than between skilled and unskilled. This is relevant because similar shifts (e.g., data scientists vs. liberal arts) emerge today in the frontier economies that adopt new general‐purpose technologies (e.g., machine learning). Thus, this paper informs policymakers today on tools to counteract a potential drop in economic equality and performance that result from this adoption. Lastly, because of similarities between the mechanics of the transition and the 2022 sanctions to discourage Russia's war effort, my results highlight the importance of additional sanctions against the education system to prevent the regime's structural adaptation and preservation.